The lived experience of non-Chinese patients 'being cared for' by Chinese nurses in Beijing, China - Concepcion, Chanell Jan C.
The concept of 'being cared for' was explored from the experiences of non-Chinese patients who were recipients of nursing care by Chinese nurses. The significance of the study is to advance the knowledge of nursing as a discipline and a practice profession. Grounded on the philosophical framework congruent with hermeneutic phenomenology, this study used Van Manen's phenomenological approach and Munhall's stepwise approach as guide for the methodology of the study. Participants included eight non-Chinese patients who met the selection criteria. Face-to-face interviews were conducted in the English language and audio recordings were made and transcribed thereafter. The findings were analyzed, interpreted and presented according to the life worlds of corporeality, relationality, spatiality and temporality. Nineteen thematic categories were identified from the participants' description of being cared for by Chinese nurses, which revealed the following essential themes, namely: 1) knowing persons through intentioned care; 2) celebrating expressions of caring; 3) trusting and finding hope; and 4) navigating the now, negotiating the next. The study has potential to transform nursing practice within a sensitivity that is grounded in caring implicating disciplinary, professional, and practice perspective in settings such as Beijing, China. The findings also provide implications for nursing research and education